2010
DOI: 10.1088/1742-6596/222/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of an accelerating cosmology in Rastall's theory

Abstract: In an attempt to look for a viable mechanism leading to a present-day accelerated expansion, we investigate the possibility that the observed cosmic speed up may be recovered in the framework of the Rastall's theory, relying on the non-conservativity of the stress-energy tensor, i.e. T µ ν;µ = 0. We derive the modified Friedmann equations and show that they correspond to Cardassian-like equations. We also show that, under suitable assumptions on the equation of state of the matter term sourcing the gravitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 22 publications
0
44
0
1
Order By: Relevance
“…Therefore, because λ is constant and the R(4κ λ − 1) = κ T condition applies to all spacetimes and energy-momentum sources, the κ λ = 1 4 case is not allowed [23]. More studies on the various aspects of this theory can be found in [74,[77][78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: A Brief Review On the Rastall Theorymentioning
confidence: 99%
“…Therefore, because λ is constant and the R(4κ λ − 1) = κ T condition applies to all spacetimes and energy-momentum sources, the κ λ = 1 4 case is not allowed [23]. More studies on the various aspects of this theory can be found in [74,[77][78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: A Brief Review On the Rastall Theorymentioning
confidence: 99%
“…Besides, since the time-time component of the Ricci tensor (R 00 ) should meet the Newtonian limit [47,50,66], we get…”
Section: A Brief Review On the Rastall Theorymentioning
confidence: 99%
“…(51) gives a lower bound for α, and therefore, we should have 1−γ γ < α < 1 to meet the the asymptotically flat condition (α < 1). Inserting (50) and (49) into (48), one can obtain…”
Section: Wormholes With Constant Effective State Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…This framework has been attracted some attentions over the last few years, and some results have been already obtained, both related to astrophysical [2][3][4][5][6][7][8][9] and cosmological solutions [10][11][12][13][14][15][16]. In particular, black holes solutions surrounded by exotic matter fields have been obtained based on the idea developed by Kiselev [17], who states that one should consider astrophysical solutions surrounded by a dark energy field, in accordance with the recent cosmological observations about the acceleration of the universe.…”
Section: Introductionmentioning
confidence: 99%